Bending, buckling and free vibration analyses of shallow-to-deep FG curved sandwich beams using a global–local refined shear deformation theory. (June 2023) - Lezgy-Nazargah, M.; Karamanli, Armagan; Vo, Thuc P.
Abstract: This paper investigates the bending, vibration, and buckling behaviour of functionally graded (FG) curved sandwich beams using a global–local refined shear deformation theory. Material properties of these beams are varied through the thickness according to the power-law distribution. A beam element with a combination of Hermite cubic and quadratic Lagrange shape functions is developed to solve the problems. The obtained results are compared with the results from finite element software (ABAQUS), and other higher-order beam theories. It can be observed that the present model can predict accurately static, vibration, and buckling responses of both shallow and deep FG sandwich beams with arbitrary boundary conditions.